Pengaruh Self-Efficacy dan Perhatian Orang Tua Terhadap Hasil Belajar Matematika Siswa SMP - Idris, Mustamin; Rifal, Mohammad; Meinarni, Welli; Rochaminah, Sutji (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This study aims to: (1) Determine whether or not there is a significant influence of self-efficacy on mathematics learning outcomes for junior high school students in Toribulu District (2) To determine whether or not there is a significant influence of parental attention on mathematics learning outcomes for junior high school students in Toribulu District (3) ) Knowing whether or not there is a significant influence of self-efficacy and parental attention on the mathematics learning outcomes of junior high school students in Toribulu District. This research is an ex-post facto research. The population in this study were class VIII students of junior high schools in Toribulu District who were enrolled in the 2022/2023 academic year. The sample in this study were 64 students. The data analysis technique used is multiple regression analysis using SPSS 25. The results of this study indicate that at a significance level of 5% (1) there is a significant effect of self-efficacy on mathematics learning outcomes for junior high school students in Toribulu District of 13.2% (2 ) there is a significant effect of parental attention on mathematics learning outcomes for junior high school students in Toribulu District by 16.7% (3) there is a significant effect of self-efficacy and parental attention on mathematics learning outcomes for junior high school students in Toribulu District by 22.4%.